DEMAND CHAIN MANAGEMENT PERFORMANCE ASSESSMENT AND STRATEGY DEVELOPMENT OF VIRGIN COCONUT OIL INDUSTRY CASE STUDY: BUMDES BUMI LESTARI - Komang Ayu Intan Ginanti; Rachmawati Wangsaputra; Irayanti Adriant (Journal of Industrial Engineering Management, 2020)
Virgin Coconut Oil BUMDes Bumi Lestari has supply chain and demand chain activities. There was an imbalance in oil production which reached 1,000 liters per month with a relatively low sales volume. The aim of this research is to apply demand chain management performance assessment on a Virgin Coconut Oil BUMDes Bumi Lestari, Desa Selemadeg, Kec. Selemadeg, Kab. Tabanan. The method used in this research is performance appraisal with the demand chain operation reference model approach, AHP weighting, OMAX, traffic light system, and SWOT analysis. The results showed that the demand chain management  performance in the BUMDes Bumi Lestari Virgin Coconut Oil business was 6,388 which was in the range of 3.01 ≤ 6,388 ≤ 8.00 (quite good). The results of the SWOT analysis recommend improvements in performance such as maintaining cooperation with suppliers, maintaining cooperation with farmer groups, maintaining the quality of Virgin Coconut Oil, improving customer service, adding workers to manage marketing, improving promotional strategies, optimizing village transportation, differentiating target of fill rates , response time, and average days per schedule change based on customer type, cooperating with the Virgin Coconut Oil derivative product industries, evaluation of customer satisfactions, and cooperating with competitors